Design is difference : 20 years of AGideas - Cato, Ken; Darbyshire, Katie (Shenyang, Lioning : Liaoning Science & Technology Publishing House, 2010)
Statement of responsibility from colophon."agideas is one of the largest and most prestigious creative events in the world, organised and presented by the Design Foundation and held annually in Melbourne Australia"--Front inside dustjacket flap.
Keywords: AGideas; Commercial art; Design